2000
DOI: 10.1007/bf02464324
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of laccase and cellulase in relation to fruit body formation in the mycelium of Lentinula edodes on a sawdust-based substrate

Abstract: Extracellular enzyme activities of laccase and cellulase and their transcriptional regulation were investigated at various growth stages in a sawdust-based substrate for Lentinula edodes. Changes of laccase and cellulase activities revealed a clear relationship with fruit body development stages, Laccase and cellulase activities were regulated at the level of gene transcription, The level of laccase mRNA was maximal at the fully colonized stage and declined during fruit body development. Cellulase mRNA began t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…At the end of colonization, just before fruiting, a second cycle of endoglucanase activity was observed. Decrease of laccase activity and a complementary increase in the cellulose activity has been associated with primordium formation (Ohga 1992;Ohga et al 2000). Through this pattern, at the sporophore production phase the polysaccharides are easily available as carbon source to support fructification process.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the end of colonization, just before fruiting, a second cycle of endoglucanase activity was observed. Decrease of laccase activity and a complementary increase in the cellulose activity has been associated with primordium formation (Ohga 1992;Ohga et al 2000). Through this pattern, at the sporophore production phase the polysaccharides are easily available as carbon source to support fructification process.…”
Section: Discussionmentioning
confidence: 97%
“…Ohga et al (2000), studying laccase and cellulose activity changes of L. edodes during colonization and fruiting stages on sawdust based substrate, demonstrated that secretion of the enzymes is controlled at the level of gene transcription. Cavallazzi et al (2004) demonstrated different behavior of L. edodes strains regarding lignocellulolytic enzymes profiles in SSF of eucalyptus bark-based medium, particularly during the colonization phase.…”
Section: Discussionmentioning
confidence: 98%
“…CMCase activities also decreased after mushroom fruiting in most SCs tested. It is known that high CMCase activities are associated with the fruiting period, and Ohga et al [32] reported that cellulase messenger RNA (mRNA) transcripts were maximally [38] also reported high cellulase productivity in the second month, which occurred during the fruiting phase of the Pleurotus spp. There was no correlation between CMCase activities and fruit-body production.…”
Section: Ligninolytic Enzyme Activitymentioning
confidence: 98%
“…Therefore fruit bodies, more than mycelia in general, are important in the context of nature conservation and management. Of course, fruit bodies have specific functional role(s) : (1) in the dissemination of spores for the establishment of new mycelia, or perhaps for the genetic adaptation of existing ones or even for the prevention of gene flow (Fries 1981, Gregory 1984 ; (2) on micro-and macrofauna due to their food value (Avila, Johanson & Bergstrom 1999, North, Trappe & Franklin 1997 ; and (3) maybe on soil mineralisation if developmentally regulated extracellular enzyme systems and differential resource utilisation as in Agaricus bisporus and Lentinula edodes (Turner et al 1975, Wood & Goodenough 1977, Ohga et al 2000 are common.…”
Section: Introductionmentioning
confidence: 99%